Circulating tumor DNA alterations in patients with metastatic castration‐resistant prostate cancer. Issue 9 (8th January 2019) - Sonpavde, Guru; Agarwal, Neeraj; Pond, Gregory Russell; Nagy, Rebecca J.; Nussenzveig, Roberto H.; Hahn, Andrew W.; Sartor, Oliver; Gourdin, Theodore Stewart; Nandagopal, Lakshminarayanan; Ledet, Elisa M.; Naik, Gurudatta; Armstrong, Andrew J.; et al.
Abstract: Background: Because cell‐free DNA (cfDNA) analysis facilitates the noninvasive genomic profiling of metastatic castration‐resistant prostate cancer (mCRPC), the authors evaluated the association between cfDNA alterations and outcomes and evolution with therapy. Methods: Patients with mCRPC underwent cfDNA genomic profiling using Guardant360, which examines major cancer‐associated genes. Clinical factors, therapy information, failure‐free survival, and overall survival (OS) were obtained for select patients. The association between genomic alterations and outcomes was investigated. Results: Of 514 men with mCRPC, 482 (94%) had ≥1 circulating tumor DNA (ctDNA) alteration. The most common recurrent somatic mutations were in TP53 (36%), androgen receptor ( AR ) (22%), adenomatous polyposis coli ( APC ) (10%), neurofibromin 1 ( NF1 ) (9%), epidermal growth factor receptor ( EGFR ), catenin beta‐1 ( CTNNB1 ), and AT‐rich interactive domain‐containing protein 1A ( ARID1A ) (6% each); and BRCA1, BRCA2, and phosphatidylinositol‐4, 5‐bisphosphate 3‐kinase catalytic subunit alpha ( PIK3CA ) (5% each) The most common genes with increased copy numbers were AR (30%), MYC (20%), and BRAF (18%). Clinical outcomes were available for 163 patients, 46 of whom (28.8%) were untreated for mCRPC. A higher number of ctDNA alterations, AR alterations, and amplifications of MYC and BRAF were associated with worse failure‐free survival and/or OS. On multivariable analysis, MYC amplification remained significantly associated with OS. Prior therapy and serial profiling demonstrated the evolution of alterations in AR and other genes. Conclusions: ctDNA frequently was detected in this large cohort of "real‐world" patients with mCRPC, and the alterations appeared to be similar to previously reported tumor tissue alterations. A higher number of alterations, and AR and MYC alterations, appear to compromise clinical outcomes, suggesting a role for immune checkpoint inhibitors and novel AR and BET inhibitors in selected patients. Abstract : Circulating tumor DNA frequently is detected in patients with advanced prostate cancer, and alterations are similar to those noted in tumor tissue. Androgen receptor alterations frequently evolve, and are associated with poor outcomes.